Answer:
First, we know that:
cot(x) = cos(x)/sin(x)
csc(x) = 1/sin(x)
I can't know for sure what is the exact equation, so I will assume two cases.
The first case is if the equation is:
[tex]\frac{cot(x)}{sin(x)} - csc(x)[/tex]
if we replace cot(x) and csc(x) we get:
[tex]\frac{cot(x)}{sin(x)} - csc(x) = \frac{cos(x)}{sin(x)} \frac{1}{sin(x)} - \frac{1}{sin(x)}[/tex]
Now let's we can rewrite this as:
[tex]\frac{cos(x)}{sin(x)} \frac{1}{sin(x)} - \frac{1}{sin(x)} =\frac{cos(x)}{sin^2(x)} - \frac{1}{sin(x)}[/tex]
[tex]\frac{cos(x)}{sin^2(x)} - \frac{sin(x)}{sin^2(x)} = \frac{cos(x) - sin(x)}{sin^2(x)}[/tex]
We can't simplify it more.
Second case:
If the initial equation was
[tex]\frac{cot(x)}{sin(x) - csc(x)}[/tex]
Then if we replace cot(x) and csc(x)
[tex]\frac{cos(x)}{sin(x)}*\frac{1}{sin(x) - 1/sin(x)} = \frac{cos(x)}{sin(x)}*\frac{1}{sin^2(x)/sin(x) - 1/sin(x)}[/tex]
This is equal to:
[tex]\frac{cos(x)}{sin(x)}*\frac{sin(x)}{sin^2(x) - 1}[/tex]
And we know that:
sin^2(x) + cos^2(x) = 1
Then:
sin^2(x) - 1 = -cos^2(x)
So we can replace that in our equation:
[tex]\frac{cos(x)}{sin(x)}*\frac{sin(x)}{sin^2(x) - 1} = \frac{cos(x)}{sin(x)}*\frac{sin(x)}{-cos^2(x)} = -\frac{cos(x)}{cos^2(x)}*\frac{sin(x)}{sin(x)} = - \frac{1}{cos(x)}[/tex]